The Role of the School Committee in Infrastructure Management (A Case Study at MTsN 11 Agam): Peran Komite Sekolah Terhadap Manajemen Sarana Prasarana (Studi Kasus Pada MTsN 11 Agam) - Arif Fiandi (Journal of Management Specialists, 2023)
The aim of this research is to determine the role of the school committee in infrastructure management at MTsN 11 Agam. The research method used is descriptive qualitative. MTsN 11 Agam is built on a waqf (endowment) land managed by a foundation. The foundation has not yet agreed to transfer the land certificate into the name of the government. This condition has resulted in MTsN 11 Agam not being able to receive government-funded infrastructure assistance, such as the construction of new buildings. The foundation is responsible only for land acquisition, not for other infrastructure matters. One possible solution to this issue is through the role of the school committee at MTsN 11 Agam. The purpose of this research is to investigate the role of the school committee in infrastructure management at MTsN 11 Agam. The research method used is qualitative. The research uses the school committee members at MTsN 11 Agam as the population, which consists of 11 individuals. Data collection is conducted through interviews. The results of this research illustrate that the school committee at MTsN 11 Agam plays a role in infrastructure management, particularly in the procurement of new classroom buildings.